2022
DOI: 10.3390/antibiotics11111544
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Outbreak on the Antibiotic Use Patterns among a Rural Community Population in Eastern China

Abstract: There are growing concerns that the coronavirus disease of 2019 (COVID-19) pandemic may change antibiotic use patterns and accelerate antibiotic resistance, but evidence from the community level is lacking. This study aims to estimate the impact of the COVID-19 outbreak on the antibiotic use patterns among a community population in Eastern China. A self-administered medicine diary was used to collect information on antibiotic use from July 2019 to June 2021 among a rural community in Eastern China. We analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Pakistan has one of the highest burdens of infectious diseases in the world [ 13 , 14 , 24 ]. To make matters worse, growing economic and financial fragility in the aftermath of the COVID-19 pandemic, combined with rapidly changing climate and natural disasters, put Pakistan at high risk of a national health crisis brought on by infectious diseases [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pakistan has one of the highest burdens of infectious diseases in the world [ 13 , 14 , 24 ]. To make matters worse, growing economic and financial fragility in the aftermath of the COVID-19 pandemic, combined with rapidly changing climate and natural disasters, put Pakistan at high risk of a national health crisis brought on by infectious diseases [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a higher HAI rate was reported in Nanjing, China in 2020 ( 14 ). A similar study found that during the COVID-19 epidemic, antibiotic use increased by 137% and antibiotic use patterns significantly changed among a rural community in Eastern China ( 15 ). However, the analysis of nationwide procurement data revealed a different result that antibiotic-defined daily doses per 1,000 inhabitants per day dropped in 2020 ( 16 ).…”
Section: Introductionmentioning
confidence: 88%
“…China also tightened drug selling to treat COVID-19-related symptoms as part of its zero-COVID efforts, which contributed to lessened self-medication with antibiotics. 3 Therefore, antimicrobial resistance has not been seen as an urgent issue, at least until China relaxed its zero-COVID policy in early December, 2022. The current surge of SARS-CoV-2 infections across China will lead to an increase in the use of antibiotics, which will exacerbate the irrational use of antibiotics seen before the COVID-19 era.…”
mentioning
confidence: 99%